Peningkatan Citra Pangan Lokal Nisan dan Oluo Sebagai Oleh-oleh Wisata Rumah Lontiok di Desa Kuok Kecamatan Kuok, Kabupaten Kampar, Provinsi Riau - Rahmayuni, Rahmayuni; Nopiani, Yanti; Pramana, Angga; Juarsa, Rahmadini Payla; Hasnah, Nur; Yunita, Imelda; Kurniawan, Mhd. Andry; Zalfiatri, Yelmira (Unri Conference Series: Community Engagement, 2024)
The traditional food products of nisan and oluo are local heritage items obtained through the process of menggelek tobu. As local products, nisan and oluo have rich and distinctive cultural value. This study intends to explore the significant role that labeling and packaging design have in promoting and spreading local culture to the larger community, as well as in improving the perception of local nisan and oluo. Incorporating cultural components such as symbols, theme colors, patterns, and language into packaging design can give it a distinctive personality and attract customers. When packaging design effectively portrays the cultural richness and history of a region, local products like nisan and oluo become more appealing and instill a sense of pride in the local community. The results indicate that using cultural information on packaging design and labeling containing cultural information can be a useful strategy improving the perception of local nisan and oluo food products and bringing culture to a larger audience. In the era of globalization, efforts to preserve cultural diversity and promote local products should be recognized and strengthened through smart and sustainable packaging design. Local products can therefore be a powerful representation of valuable cultural identity and contribute positively to the economy and cultural awareness both nationally and internationally.